Penggalangan Bank Sampah dan Pengolahan Sampah Menjadi Produk Seni, Eco-brick dan Eco-Enzime Di Desa Gunung Rajak, Lombok Timur. - Darunnafis, Moh. Khazani; Ira Lestari; Ratna Ayu Istiani; Yasmin Maulani; Zinnur Aini; M. Aprilian Syahputra; Fajrul Falah; Rifyal Ghaizi Al Gazali; Salma; Sugi Hartuti; Suripto (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Gunung Rajak Village, East Lombok has an area of ​​624 hectares and a population of 6,875 people. The main problem faced by the village is the low level of community awareness and independence in handling waste. In the previous year, this village produced 3,322.5 kg of waste per day, more than 60% of which had not been managed optimally. PMD Unram KKN is very relevant to be implemented in this village with the general aim of increasing community awareness and independence in dealing with waste problems in Gunung Rajak Village with the specific aim of increasing community knowledge and skills in implementing the waste bank program, processing inorganic waste into art products and ecobricks and processing kitchen waste into ecoenzymes, maintaining environmental health and increasing community participation in planting trees in the Nenuju Green and Independent Village program. This activity was carried out by Mataram University students who were accompanied by supervisors, the Head of Gunung Rajak Village and his staff and partners from the local Health Service and the Mandalika Modern Nursery of the Ministry of Environment and Forestry of the Republic of Indonesia. Activities were carried out using lecture, discussion, demonstration and practice methods with POSYANDU cadres and representatives of the Gunung Rajak Village community as the target audience. The results show that 85% of participants understand the waste bank program, processing waste into art products, eco-bricks and eco-enzymes and are committed to implementing this technique in their homes. The results also show that the community has participated in planting 1000 jackfruit tree seedlings at the main point covering an area of ​​0.5 ha and other strategic points covering an area of ​​4 ha in Gunung Rajak Village